Spawn : unwanted violence - McFarlane, Todd (Image Comics, 2024)
Spawn faces a moral dilemma witnessing senseless violence, while THE FREAK uncovers "File F." As tension rises and police target SPAWN, he has to inevitably confront morality and the essence of good and evil.